Political Suppression or Revenue Raising? Taxing Newspapers During The French Revolutionary War - Oats, L.; Sadler, Pauline (Academy of Accounting Historians, 2004)
In 1797 the Prime Minister of Great Britain announced a substantial increase in the stamp duty on newspapers. This increase, and indeed the tax itself, has been variously represented as an attack on press freedom and an act of suppression of the working classes. This paper reconsiders these representations by reference to primary sources and concludes that tile increases in stamp duty were part of a revenue raising exercise in which taxes on a number of luxury items were increased, including newspapers which were not at the time viewed as being necessities.